IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA KELAS VI SDN BAGELENAN 03 SRENGAT BLITAR TAHUN PELAJARAN 2017/2018 - Martini Martini (Program Studi Pendidikan Guru Sekolah Dasar, 2019)
The initial observation showed that there were problems in mathematics. That is about the low activity and learning outcomes of Class VI students at SDN Bagelenan 03 Srengat Blitar. This problem is because when the learning process takes place, students only listen, record and obey the teacher's commands, so that students feel bored. The teacher only uses the lecture method without varying the other methods. The best solution about these problems is cooperative learning with STAD type. This research aiming to increasing the activity and learning outcomes of mathematics in class VI students subject matter of fraction counting operations in SDN Bagelenan 03. The type of research used is classroom action research. Data collection uses the method of observation, tests, documentation, and interviews. Data collected in the form of analysis of students' answers to the value of the first cycle test and second cycle test. The application of cooperative learning STAD type subject matter of fraction counting operations can be concluded that the activities and learning outcomes in the first cycle have met the minimum completeness criteria, while in the second cycle have increased again. The second cycle is a stabilization cycle because in the first cycle has been completed.